2020
DOI: 10.1101/2020.05.06.20089573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recurrence of SARS-CoV-2 PCR positivity in COVID-19 patients: a single center experience and potential implications

Abstract: IMPORTANCE How to appropriately care for patients who become PCR-negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still not known.Patients who have recovered from coronavirus disease 2019 (COVID-19) could profoundly impact the health care system if a subset were to be PCR-positive again with reactivated SARS-CoV-2.OBJECTIVE To characterize a single center COVID-19 cohort with and without recurrence of PCR positivity, and develop an algorithm to identify patients at high risk of rete… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 32 publications
(27 reference statements)
1
41
0
Order By: Relevance
“…Active SARS-CoV-2 viral replication in the gastrointestinal tract Since strict home quarantine measures precluded the possibility of a new infection, the virus detected in the positive retest was epidemiologically postulated to have been derived from the initial virus infection. 6,[8][9][10][11] However, experimental evidence directly supporting that conclusion has been lacking. We sequenced the viruses obtained from 42 throat and anal samples from 16 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Active SARS-CoV-2 viral replication in the gastrointestinal tract Since strict home quarantine measures precluded the possibility of a new infection, the virus detected in the positive retest was epidemiologically postulated to have been derived from the initial virus infection. 6,[8][9][10][11] However, experimental evidence directly supporting that conclusion has been lacking. We sequenced the viruses obtained from 42 throat and anal samples from 16 patients.…”
Section: Resultsmentioning
confidence: 99%
“…This causes public health concerns, such as the origin of the virus in such patients, whether the virus is transmissible, and which patients will have positive retest results. Positive detection of SARS-CoV-2 in discharged patients during follow-up is usually regarded as a recurrence of the original virus after the epidemiological exclusion of a new infection 6,[8][9][10][11] based on the fact that the discharged patients underwent a 14-day home quarantine according to the Chinese government treatment guidelines. However, this postulation has seldom been experimentally supported.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the long-term outcomes among cleared SARS-CoV-2 patients has been thus far limited and often poorly defined. Some patients labeled as cleared have been shown to have a new positive test after documented negative tests, a positive test after a period of quarantine, or develop new symptoms requiring hospitalization after documented negative tests [2][3][4][5][6] . The former case is most narrowly suggestive of delayed viral shedding, false positives, or re-infection while the latter case allows for a more broader interpretation of possible outcomes after clearance to also include delayed complications of the index hospitalization and manifestations of a systemic inflammatory response 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent case series 8 reported four patients with apparent SARS-CoV-2 reinfection after an index hospitalization, despite resolution of symptoms and radiographic abnormalities and two consecutive negative tests separated by a day. A single center cohort study of 414 patients with SARS-CoV-2 reported a reinfection rate of 16.7% among cleared patients 5 , while a second cohort study of 262 patients with SARS-CoV-2 reported a reinfection rate of 14.5% among cleared patients 4 . To date, details on the outcomes of patients who require hospitalization after documented clearance of SARS-CoV-2, however, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The emerging COVID-19 pandemic caused an unexpected and large number of infections leading to significant mortality globally. Due to mandatory quarantine strategy, the rate of viral transmission has been slowed down, but there is still an urgent need to find a therapeutic agent to treat or prevent the transmission of the virus, especially in the light of possible reinfection after recovery (ALIZARGAR, 2020;ZHENG;HAO et al, 2020). SAMULSKI, 2012).…”
Section: Discussionmentioning
confidence: 99%